2015
DOI: 10.1021/acs.jpcc.5b08771
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecularly Modified Graphene for Ultrafast Responsive and Highly Stable Humidity Sensor

Abstract: We report the fabrication and detailed characterization of an ultrafast responsive, excellently stable and reproducible humidity sensor based on a supramolecularly modified graphene composite. The fabricated humidity sensors exhibited a response and recovery time of less than 1 s, which is the lowest among the values found in the literature. In addition, various sensing performances of the fabricated humidity sensors were studied in detail, and the corresponding kinetic model and mechanism have also been deduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…Another explanation is the formation of electron charge carrier traps by dissociation of water molecules into hydronium ions (H 3 O + ). Water molecules are readily dissociated by forming proton (H + ) and hydroxide ion (OH − ) . Under the sufficient water molecules, hydronium ions are easily formed by protonation of another water molecule .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation is the formation of electron charge carrier traps by dissociation of water molecules into hydronium ions (H 3 O + ). Water molecules are readily dissociated by forming proton (H + ) and hydroxide ion (OH − ) . Under the sufficient water molecules, hydronium ions are easily formed by protonation of another water molecule .…”
Section: Resultsmentioning
confidence: 99%
“…Water molecules are readily dissociated by forming proton (H + ) and hydroxide ion (OH − ) . Under the sufficient water molecules, hydronium ions are easily formed by protonation of another water molecule . The n RGO fiber exhibits n ‐type property with majority charge carriers of electrons due to n ‐type dopant of nitrogen .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, modified doped graphene (GO) sensors have fast response to humidity due to GO's high charge carrier mobility and content of surface defects and residual oxygen-containing groups (carboxyl, epoxy, hydroxyl, etc.) [10][11][12][13]. Wearable electronic textile humidity sensors based on carbon nanotubes and composite fibers have also been developed [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al 22 fabricated Ag nanowires with DNA as a template and reported that the Ag-DNA network showed a current increase of more than 400%. Wang et al 23 fabricated sensors based on NAgraphene modied with Ag nanoparticles, which showed a fast response speed ($1 second). Therefore, the combination of Ag and GO could be expected to create new functional nanocomposites with excellent humidity sensing properties.…”
Section: Introductionmentioning
confidence: 99%